2002
DOI: 10.1113/jphysiol.2001.014639
|View full text |Cite
|
Sign up to set email alerts
|

A Ca2+‐inhibited non‐selective cation conductance contributes to pacemaker currents in mouse interstitial cell of Cajal

Abstract: Considerable evidence suggests that interstitial cells of Cajal (ICC) are the pacemakers cells in gastrointestinal (GI) muscles (e.g. Langton et al. 1989; Ward et al. 1994; Huizinga et al. 1995; Thomsen et al. 1998; Koh et al. 1998; Dickens et al. 1999). Freshly isolated (Langton et al. 1998) and cultured ICC (Thomsen et al. 1998; Koh et al. 1998) generate spontaneous electrical slow waves and pacemaker currents. Absence of ICC in tissues results in loss of slow waves (Torihashi et al. 1995; and for see revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(115 citation statements)
references
References 33 publications
5
109
0
1
Order By: Relevance
“…Electrical slow waves are a fundamental property of phasic GI muscles, and these events activate periodic Ca 2ϩ entry and regulate contractions in electrically coupled smooth muscle cells. A Ca 2ϩ -inhibited, nonselective cation conductance contributes to the pacemaker current that initiates slow wave activity (10,11). In the present study, we identified a molecular entity, TRPC4, that shares many similarities with native pacemaker channels.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Electrical slow waves are a fundamental property of phasic GI muscles, and these events activate periodic Ca 2ϩ entry and regulate contractions in electrically coupled smooth muscle cells. A Ca 2ϩ -inhibited, nonselective cation conductance contributes to the pacemaker current that initiates slow wave activity (10,11). In the present study, we identified a molecular entity, TRPC4, that shares many similarities with native pacemaker channels.…”
Section: Discussionmentioning
confidence: 78%
“…Niflumic acid and DIDS have been shown to block the Ca 2ϩ -inhibited, nonselective cation currents in ICC (10). Therefore, we tested the effects of niflumic acid on HEK-293 cells stably expressing TRPC4␤.…”
Section: Molecular Features Of Trp Channelsmentioning
confidence: 99%
“…It is also possible that intracellular Ca 2+ causes inhibition of the non-selective cation current that underlies pacemaker activity. 3,24,30 Refractoriness is also observed in the heart, where the amplitude of premature action potentials and the resulting contractions are reduced in amplitude and force. 1 Our studies suggest that the long refractory periods observed for slow waves 24 is a consequence of the Ca 2+ dynamics in ICC-MY rather than a property of the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Discovering the molecules involved in the generation of pacemaker activity in ICCs may lead to dramatic new therapies for chronic GI diseases that result in lifelong suffering. The pacemaker activity in the murine small intestine is due mainly to periodic activation of nonselective cation channels (NSCCs) (Koh et al, 2002) and we suggested that the electrophysiologi- cal and pharmacological properties of TRPM7 and the NSCCs in ICCs were the same and, therefore, the TRPM7 protein is an essential molecular component of NSCC in ICCs (Kim et al, 2005). Also, Zhu et al (2009) suggested that Ca 2+ -activated Clconductance is also involved in slow wave current in ICC and that ANO1 participates in pacemaker activity.…”
Section: Discussionmentioning
confidence: 98%
“…Slow waves propagate within ICC networks, conduct into smooth muscle cells via gap junctions, and initiate phasic contractions by activating Ca 2+ entry through L-type Ca 2+ channels. The pacemaker activity in the murine small intestine is due mainly to periodic activation of nonselective cation channels (NSCCs) (Koh et al, 2002) or Cl -channels (Huizinga et al, 2002;Zhu et al, 2009). ICCs also mediate or transduce inputs from the enteric nervous system.…”
Section: Introductionmentioning
confidence: 99%